Kesiapan Siswa SMP Negeri 2 Siberut Utara dalam Menghadapi Asesmen Nasional Berbasis Komputer - Manik, Manganju (STAI Auliaurrasyidin Tembilahan, 2022)
The Computer-Based National Assessment (ANBK) is a government program that aims to map the education quality of primary and secondary school in Indonesia. The purpose of this study was to find out: (1) a description of the student’s readiness in facing the ANBK, (2) what factors were the obstacles for student in preparation for ANBK. This type of research is qualitative research with a case study approach regarding the student’s readiness Utara in facing ANBK. Preparations made by students in facing ANBK include participating in the socialization carried out by teachers who serve as proctors and technicians. Then students participating in computer use training accompanied by teachers which are carried out after school. During this training the teacher provides motivational support to students to stay motivated, enthusiastic, and not worried in facing ANBK There are several obstacles to students' readiness to face ANBK, namely students have low technological literacy, limited available computer equipment, limited power sources as a resource for using computer equipment, and limited internet networks causing students to not be able to participate in simulations on the ANBK website. Although accompanied by obstacles during the preparation process, students have good readiness to participate in the implementation of ANBK, this can be proven by the implementation of ANBK well.